LITERATURE STUDY ON THE ROLE OF THE TEACHING FACTORY MODEL IN IMPROVING THE WORK READINESS OF VOCATIONAL SCHOOL STUDENTS - Andi Rizka Ekaputri; Elfira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of the TeachingFactory (TeFa) learning model in improving thecompetence and work readiness of Vocational HighSchool (SMK) students. The research uses a literaturestudy method by collecting, reviewing, and analyzingvarious relevant previous studies from nationaljournals, international journals, and scientificproceedings. The selection of data sources is carriedout based on the criteria for the suitability of researchvariables, the use of standard language, publicationsin the last five years, and have been published in scientific journals. The data analysis technique usesthe content analysis method through the process ofselecting, comparing, merging, and interpreting data toobtain valid conclusions. The results of the study showthat the Teaching Factory model plays a significant rolein improving students' technical competencies (hardskills) and non-technical skills (soft skills), such as discipline, responsibility, communication, teamwork, adaptability, and confidence. In addition, the TeachingFactory is able to create a real work experiencethrough production-based learning according toindustry standards so as to increase students' workreadiness, practical ability, learning motivation, andcareer readiness. The success of the implementationof the Teaching Factory is also influenced by thealignment of the curriculum and the school'spartnership with the industrial world. Although thereare still obstacles in the form of limited facilities, teacher competence, and industrial cooperation, theTeaching Factory remains an effective vocationallearning model in preparing competent, adaptive, andjob-ready vocational school graduates.